Advanced Personal Comfort System (APCS) for the workplace: a review and case study - Shazad, Sally; Calautit, John Kaiser; Calautit, Katrina; Hughes, Ben Richard; Angelo, Aquino (Elsevier, 2018)
The aim of this research is to investigate the application and performance of an advanced personal comfort system, a thermal chair, using Computational Fluid Dynamics (CFD), Building Energy Simulation (BES) and field test analysis. The thermal chair permits individual control over their immediate thermal environment without affecting the thermal environment and comfort of other occupants. A comprehensive review on the existing research on the design and performance of various personalised thermal control systems was carried out. A prototype of a thermal chair was designed for the study and tested in an open plan office during the heating season in Leeds, UK. 45 individuals used the chair in their everyday context of work and a survey questionnaire was applied to record their views of the thermal environment before and after using the chair. The performance of the chair was investigated through CFD simulations (ANSYS Fluent) providing a detailed analysis of the thermal distribution around a thermal chair with a manikin. Furthermore, a model of a three-story office building with thermal chairs were created and simulated in the commercial BES software, IES Virtual Environment. The benchmark model of the building was validated with previous work and good agreement was observed. The results showed that user thermal comfort can be enhanced by improving the local thermal comfort of the occupant. The additional plug-load energy from the thermal chair was significantly less as compared to the heating energy saved by adjusting the heating set point by 2°C during the heating season. Monthly heating energy demand was reduced by 27% on January and 25.4% on February. Furthermore, the results of the field study revealed 20% higher comfort and 35% higher satisfaction level, due to the use of thermal chair.